The problem-solving ability in terms of self-efficacy with Creative Problem-Solving Learning - Wulandari, Meidila; Asikin, Mohammad (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aims to determine the quality of learning with the CPS model on PSA, the CPS learning model to achieve learning mastery and to describe PSA in terms of self-efficacy. The research method used in this study was a mixed or combination method. The population in this study were eighth-grade students of Junior High-School 1 Moga in the academic year of 2018/2019, and by using random sampling the class VIII H was chosen as the experimental class. The data collection methods used in this study were documentation, observation, tests, interviews, and self-efficacy scale. The results of this study indicate that (1) The quality of learning with the CPS model on students’ PSA is very good; (2) Students’ PSA in the CPS learning model achieve learning mastery; (3) Students with high problem-solving ability are able to achieve all indicators of problem-solving ability and self-efficacy perfectly, students with moderate problem-solving ability have not been able to achieve all indicators of problem-solving ability and self-efficacy perfectly, and students with low problem-solving ability has not been able to reach all indicators of problem-solving ability and self-efficacy.